Are Humanities Heading for Extinction? Analysis of Anthropocene Ecocriticism, Geo-Ecocriticism, and Islamecocriticism - Inas Samy Abolfotoh (IAIN Padangsidimpuan, 2023)
Serious concerns have been circulating in academia regarding humanities and how they have been relegated to the backbenches. Data reveal a remarkable decline in submissions for humanities if compared to non-humanities. The current paper proposes that despite this decline, humanities have always been and will continue to be a moving force in shaping intellectual attitudes worldwide. To prove this standpoint, the author employs ecocriticism and eco-poetry as influential sub-disciplines of humanities. With the rocket-speed changeability of the present time, ecocriticism and eco-poetry play a crucial role in judging, evaluating, or even changing the course of cultural advancements if they venture into destructive paths. In other words, ecocritical theory is concerned with monitoring and unveiling versatile anthropocentric activities, most of which are destructive to nature. Fortunately, with the help of authors writing under the influence of ecocriticism, the devastation of many natural spots came to an end. Thus, the study begins by introducing some important phases of the ecocritical project like Anthropocene ecocriticism, Geo-ecocriticism, and Islamecocriticism. Then, an Islamecocritical analysis of